Тематический подход в языковом образовании - Дощинский, Роман (Զանգակ հրատ.)
Հոդվածը նվիրված է լեզվական կրթության նկատմամբ տեսական մոտեցմանը: Այն հեղինակի դիտանկյունից պետք է ենթադրի սովորողների կապակցված խոսքի ձևավորում` հիմնված հաղորդակցության նպատակներով տեքստերի կիրառման վրա, որոնք էականորեն հարստացնում են լեզվի դասը՝ ապահովելով աշխարհի և մարդկանց նկատմամբ աշխարհընկալումը: The paper deals with the comprehensive approach to language education. From the author’s point of view language education should involve formation of coherent speech that is based on the use of the text for communication. The text for communication implies cardinal expansion of the language lesson which provides thematic vision of the world and people.
Keywords: Теория языка